HUBUNGAN ASUPAN ENERGI KEPATUHAN MINUM OBAT DENGAN STATUS GIZI PASIEN TUBERCULOSIS PARU DI WILAYAH KERJA PUSKESMAS GENUK KOTA SEMARANG - Dwi Putriyani Rizqiyah; Muflihah Isnawati (JURNAL RISET GIZI, 2015)
Background: the incidence of tuberculosis is very closely related to the nutritional status of sufferers. Previous research stated that 56.8% of TB patients had a body mass index (BMI) of less than normal (18.5 kg / m2). Poor nutritional status in TB patients can be caused by factors such as inadequate energy intake and infection conditions. In addition, adherence to taking medication is also an important factor for improving the nutritional status of tuberculosis patients. Objective: to analyze the relationship of energy intake, adherence to taking medication with the nutritional status of pulmonary tuberculosis patients in the working area of the Genuk City Health Center Semarang. Methods: this study is a descriptive analytic study with a Cross Sectional approach. The research subjects were 13 adult tuberculosis patients who were still undergoing treatment in the working area of the Genuk City Health Center in Semarang. Data collected included energy intake data, medication adherence and nutritional status. Statistical analysis using Pearson product moment correlation and Fisher Exac. Results: there is no correlation between energy intake, adherence to taking medication and nutritional status of pulmonary tuberculosis patients in the working area of the Genuk City Health Center Semarang